Impact of the Ga flux incidence angle on the growth kinetics of self-assisted GaAs nanowires on Si(111). Issue 11 (15th October 2019) - Vettori, Marco; Danescu, Alexandre; Guan, Xin; Regreny, Philippe; Penuelas, José; Gendry, Michel
Abstract : In this work we show that the incidence angle of group-III element fluxes plays a significant role in the diffusion-controlled growth of self-assisted III–V nanowires by molecular beam epitaxy. Abstract : In this work we show that the incidence angle of group-III element fluxes plays a significant role in the diffusion-controlled growth of III–V nanowires (NWs) by molecular beam epitaxy (MBE). We present a thorough experimental study on the self-assisted growth of GaAs NWs by using a MBE reactor equipped with two Ga cells located at different incidence angles with respect to the surface normal of the substrate, so as to ascertain the impact of such a parameter on the NW growth kinetics. The as-obtained results show a dramatic influence of the Ga flux incidence angle on the NW length and diameter, as well as on the shape and size of the Ga droplets acting as catalysts. In order to interpret the results we developed a semi-empirical analytical model inspired by those already developed for MBE-grown Au-catalyzed GaAs NWs. Numerical simulations performed with the model allow us to reproduce thoroughly the experimental results (in terms of NW length and diameter and of droplet size and wetting angle), putting in evidence that under formally the same experimental conditions the incidence angle of the Ga flux is a key parameter which can drastically affect the growth kinetics of the NWs grown by MBE.